The role of public health insurance in protecting against the costs of ill health: Evidence from Mexico - Belén Sáenz de Miera Juárez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In the absence of health insurance, households have to self-insure against the risk of ill health, which may involve the use of mechanisms that have long-term consequences. This study analyses whether Mexican households are able to smooth consumption after severe health shocks, as well as the contribution of public health insurance in the form of social security and, more recently, the Seguro Popular programme. Using data from the Mexican Family Life Survey, a nationally representative longitudinal survey, the results indicate that unexpected health events such as accidents and deterioration in physical capacity are associated with large declines in non-medical consumption. Social security seems to provide protection against both types of shocks, but the endogeneity-corrected estimates indicate that the Seguro Popular programme only protects consumption against accidents. This suggests that income losses associated with disability shocks, for which the programme does not offer protection, are likely larger than medical care expenditures, and poses the question of whether other social security benefits, such as disability insurance, should also be extended to non-beneficiaries.
Keywords: I13; I38; 330; public insurance; consumption; catastrophic risks; health shocks